2014
DOI: 10.2196/jmir.2965
|View full text |Cite
|
Sign up to set email alerts
|

Relative Validity of Micronutrient and Fiber Intake Assessed With Two New Interactive Meal- and Web-Based Food Frequency Questionnaires

Abstract: BackgroundThe meal- and Web-based food frequency questionnaires, Meal-Q and MiniMeal-Q, were developed for cost-efficient assessment of dietary intake in epidemiological studies.ObjectiveThe objective of this study was to evaluate the relative validity of micronutrient and fiber intake assessed with Meal-Q and MiniMeal-Q. The reproducibility of Meal-Q was also evaluated.MethodsA total of 163 volunteer men and women aged between 20 and 63 years were recruited from Stockholm County, Sweden. Assessment of micronu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 28 publications
2
44
0
Order By: Relevance
“…Moreover, the daily emissions of CO 2 e was comparable to other studies based on individually assessed dietary intake using FFQ [68]. The dietary assessment method that was used, Meal-Q, was developed and validated by us for the LifeGene study [18, 19], and showed strong validity and reproducibility [21]. A limited number of studies have analyzed CO 2 e from self-selected diets assessed in surveys or cohort studies [69], but to our knowledge, this is the first study based on a Swedish population.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Moreover, the daily emissions of CO 2 e was comparable to other studies based on individually assessed dietary intake using FFQ [68]. The dietary assessment method that was used, Meal-Q, was developed and validated by us for the LifeGene study [18, 19], and showed strong validity and reproducibility [21]. A limited number of studies have analyzed CO 2 e from self-selected diets assessed in surveys or cohort studies [69], but to our knowledge, this is the first study based on a Swedish population.…”
Section: Discussionmentioning
confidence: 74%
“…Diet was assessed using the interactive web-and meal based FFQ called Meal-Q, described in detail elsewhere [18, 19]. Meal-Q assesses habitual dietary intake during the previous months and includes 102–174 food items, dishes, and beverages, depending on the number of follow-up questions, as well as questions about supplement use, meal patterns, and eating behavior.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last trimester of pregnancy, all women were asked to answer an online semi-quantitative FFQ [20,21] that provided intake data on food levels, as well as macro-and micronutrient levels. The questionnaire has been validated among non-pregnant adults for macro-and micronutrients against 7-day food records and doubly-labelled water.…”
Section: Data Collection and Assessment Of Dietary Intakementioning
confidence: 99%
“…Recently, two innovative dietary assessment tools for use in large-scale studies were developed; the detailed 4-day food record tool called the Riksmaten method [26], and the more rapid food frequency questionnaire called MiniMeal-Q [27,28]. The aim of this study was to use carotenoids as biomarkers of fruit and vegetable intake and alkylresorcinols as biomarkers of whole grain wheat and rye intake, when examining and comparing the ability of the two self-reported methods to capture habitual dietary intake.…”
Section: Introductionmentioning
confidence: 99%